Filtration performance of non- woven geotextiles with internally-stable and -unstable soils under dynamic loading. Issue 2 (April 2022) - Khan, M.W.; Dawson, A.R.; Marshall, A.M.
Abstract: In many applications, geotextiles are subjected to dynamic loading conditions, for example, below roads and railways, for which a Gradient Ratio (GR) test is often used to assess filtration compatibility of soil-geotextile systems. This paper presents results from GR filtration tests with internally-stable and -unstable soils under dynamic loading conditions. In the tests, four non-woven geotextiles were used with varying types of soils under a hydraulic gradient of 5. Test results were interpreted in terms of GR values, permeability values, and mass and gradation characteristics of the soil before/after testing as well as the particles passing through the geotextiles. The test results show that the dynamic loading resulted in an increase of soil migration within the soil as well as an increase in the quantity of soil passing through the geotextiles. The available criteria for evaluating the internal stability of soils are evaluated based on the experimental data. Based on the test results, improvements to filter retention design criteria are suggested which take into account the internal stability of soils under dynamic loading. Highlights: Gradient Ratio (GR) filtration tests were carried out under dynamic loading conditions. Four non-woven geotextiles were used with varying types of soils. The internal stability of the adopted soils were assessed using several existing methods from the literature. Dynamic loading resulted in an increase of soil migration within the soil as well as an increase in the quantity of soil passing through the geotextiles. Improvements to filter retention design criteria are suggested.